Tunable Neuromimetic Integrated System for Emulating Cortical Neuron Models - Grassia, Filippo; Buhry, Laure; Lévi, Timothée; Tomas, Jean; Destexhe, Alain; Saïghi, Sylvain (Frontiers in Neuroscience, 2011)
Nowadays, many software solutions are currently available for simulating neuron models. Less conventional than software-based systems, hardware-based solutions generally combine digital and analog forms of computation. In previous work, we designed several neuromimetic chips, included Galway chip that we used for this paper. These silicon neurons are based on the Hodgkin-Huxley formalism and they are optimized for reproducing a large variety of neuron behaviors thanks to tunable parameters. Due to process variation and device mismatch in analog chips, we use a full-custom fitting method in voltage-clamp mode to tune our neuromimetic integrated circuits. By comparing them with experimental electrophysiological data of these cells, we show that the circuits can reproduce the main firing features of cortical cell types. In this paper, we present the experimental measurements of our system which mimic the four most prominent biological cells: Fast Spiking (FS), Regular Spiking (RS), Intrinsically Bursting (IB) and Low Threshold Spiking (LTS) neurons into analog neuromimetic integrated circuit dedicated to cortical neuron simulations. This hardware and software platform will allow improvements the hybrid technique, also called ‘dynamic-clamp’, that consists of connecting artificial and biological neurons to study the function of neuronal circuits.